Copy-editing : - Butcher, Judith (Cambridge University Press, 1992)
This new edition has been revised and redesigned to provide an up-to-date and clearly presented source of information for editors and for all those involved in the process of preparing typescripts and illustrations for printing and publication. The copyeditor is shown as an essential link between the authors and those who work on the actual production of the publication. The copyeditor ensures that the material is well organized, consistent and properly presented and helps remove any features that might cause unnecessary difficulty, expense or delay.